Peningkatan Kemampuan Literasi Numerasi Siswa SDN 1 Pedes Melalui Program Bimbel Intensif - Arie Purwanto; Nanang Khuzaini; Nuryadi; Rusmining; Nafida Hetty Marhaeni; Muhammad Irfan Rumasoreng; Naela Faza Fariha (CV. Kurnia Grup, 2026)
This Community Service Program (PkM) aims to improve the numeracy literacy skills of students at SD Negeri 1 Pedes through intensive tutoring at the UMBY Mathematics Education Tutoring Center